PROBLEMATIKA KOLABORASI PEMBELAJARAN DARING DAN LURING DI SDN 09 MUARADUA KABUPATEN OKU SELATAN - Dwi Oksa Fitri; Karoma Karoma; Halimatussakdiah Halimatussakdiah (PAI RAFAH, 2021)
This research discusses the problem that occurs in the implementation of 2 ways of lessons. namely online learning and offline learning at the 09 Muaradua Elementary School, South OKU Regency.This research uses a qualitative research approach with a type of case study. Data collection techniques with observation, interviews, and documentation. The data analysis method used consists of three stages, namely data collection, data reduction, and concluding the final result of the study.The application of online and offline learning collaborations is carried out by dividing the time between online and offline learning. The problems during online learning, namely signal constraints, many students do not have cellphones, teachers and students are still a little technologically illiterate. The problem when learning offline is that students are sometimes reluctant to follow health protocols such as wearing masks and keeping clean their hands. With various problems from each of these lessons, it causes less conducive collaboration between these two lessons. Solutions from various parties in the school environment to overcome all problems by helping each other in the learning process.